A new transmission model in cognitive radio based on cyclic generalized polynomial codes for bandwidth reduction - Azam, Naveed Ahmed; Shah, Tariq; Andrade, Antonio Aparecido de [UNESP] (World Scientific Publishing, 2014)
The frequency spectrums are inefficiently utilized and cognitive radio has been proposed for full utilization of these spectrums. The central idea of cognitive radio is to allow the secondary user to use the spectrum concurrently with the primary user with the compulsion of minimum interference. However, designing a model with minimum interference is a challenging task. In this paper, a transmission model based on cyclic generalized polynomial codes discussed in [2] and [15], is proposed for the improvement in utilization of spectrum. The proposed model assures a non interference data transmission of the primary and secondary users. Furthermore, analytical results are presented to show that the proposed model utilizes spectrum more efficiently as compared to traditional models.
Keywords: Cyclic generalized polynomial codes; underlay model; overlay model; bandwidth AMSC: 11T71,94A15,14G50